2015
DOI: 10.1016/j.envexpbot.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of antimony and arsenic in the soils and plants in an old antimony mine

Abstract: a b s t r a c tThe speciation changes of antimony (Sb) in soil-plant system are largely unknown as compared with those of arsenic (As). In this study, indigenous plants and associated soils were sampled at the Xikuangshan Sb mine (XKS), China. The Sb in the soils (441-1472 mg/kg) were far greater than As (32-354 mg/kg), and the Sb and As availabilities in the soils, were 5.5% and 3.9% in average, respectively. HPLC-ICP-MS revealed the presence of four species of Sb in the soils and plants, including Sb III , S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…For Sb, these concentrations are well above soil background values of 0.3-8.6 mg kg −1 [48]. However, they are in line with previously found concentrations of Sb in shooting range and mining sites that range up to 17,500 mg kg −1 [5,8,22,34,49,50]. It must be noted, however, that extremely small bullet residues (<100 μm) can be present in the soil [4].…”
Section: Total Sb Concentrations In the Shooting Range Soilssupporting
confidence: 64%
“…For Sb, these concentrations are well above soil background values of 0.3-8.6 mg kg −1 [48]. However, they are in line with previously found concentrations of Sb in shooting range and mining sites that range up to 17,500 mg kg −1 [5,8,22,34,49,50]. It must be noted, however, that extremely small bullet residues (<100 μm) can be present in the soil [4].…”
Section: Total Sb Concentrations In the Shooting Range Soilssupporting
confidence: 64%
“…Although previous studies showed the presence of TMSb in plants using other 316 extractions methods [8,23,24,31] , this is the first study to provide a sufficient level of quality control to 317 ensure that TMSb is not formed during the extraction or analysis of these samples. Also, it is the first 318 time that TMSb uptake and transfer is demonstrated under controlled conditions.…”
Section: Conclusion 313mentioning
confidence: 99%
“…It is generally more mobile than other pollutants such as As and lead (Pb) [5,6] , 41 although this can change depending on the redox conditions [7] . Sb is however more available than As in 42 mining soils [8] and can thus be taken up by microorganisms or plants more easily. Indeed, concentrations 43 between 100 and 4000 mg.kg -1 have been found in plants growing in mining areas [4] .…”
Section: Introduction 33mentioning
confidence: 99%
See 1 more Smart Citation
“…Its longtime and large-scale mining and smelting has produced large amounts of smelting slag. With surface runoff and precipitation infiltration, harmful elements like Sb and the associated elements As and Hg have been released, threatening the environment and human beings [10][11][12][13][14]. When an excessive amount of Sb, As, or Hg enters the human body, it will cause diseases to the liver, skin, tumors, respiratory and cardiovascular systems, and even cancer [15][16][17][18][19].…”
mentioning
confidence: 99%